Development of HOTS Assessment Instruments in Vibration and Wave Courses - Nurhayati Nurhayati; Wahyudi Wahyudi; Syarif Lukman Hakim Alsagaf (Jurnal Pembelajaran Fisika, 2021)
This study aims to 1) produce a HOTS assessment instrument; 2) knowing the quality of the test instrument in terms of the feasibility of construction, material feasibility, and language feasibility according to the expert; and 3) knowing the quality of the test items in terms of validity, reliability, difficulty level and distinguishing power based on the test results. Research and Development were used as a research method with 4D procedural development model consists of four stages, namely: the define stage, the design stage, the development stage, and the dissemination stage. The questionnaire was used for expert judgment validation. The characteristics measurement of the HOTS items instrument including the validity, reliability, difficulty level, and distinguishing power of the questions. The HOTS assessment instrument developed was in the form of multiple-choice options with a reason based on HOTS in aspects of analyzing, evaluating, and creating. The results of expert validation show that the average item with criteria is very good in terms of content, construct, and language aspects. Instruments that have been validated and revised were tested on students who had studied vibration and wave material and the test results showed that 77% of the questions developed were of good quality with valid criteria, good distinguishing criteria, level of difficulty at moderate and easy levels and very strong reliability so that feasible and ready to be used to measure students' higher-order thinking skills in vibrations and waves material.Keywords: HOTS, Instruments test, Vibrations, and wavesDOI: http://dx.doi.org/10.23960/jpf.v9.n1.202108